The Role of Strategic Deployment in Addressing the Absence of Strategic Planning for The Distribution of Pharmacists: An Exploratory Study - Alabadi, Hashim Fawzi; Karim, Ammar Hassan (International Journal of Psychosocial Rehabilitation, 2020)
Strategic deployment is one of the concepts that has attracted the attention of literature as a core determinant of the recognition of organizations in the current millennium for their role in enhancing the prospects for organizational success. The aim of the paper is to examine the absence of strategic planning and tackle it using the strategic deployment variable. The Imam Hussein Teaching Hospital in the province of ThiQar is a sample of this research. The paper adopts a descriptive approach by using the contents of the deductive analysis in the fields of theoretical framing and realistic testing of the study model and hypotheses. We distributed a questionnaire to 100 pharmacists working in the sample hospital. The questionnaire tool that was designed according to the quintile (Likert) penthouse, as the researchers relied on tests for measurements employed in International studies approved after they have been adapted for the purposes of the current study and have been tested for reliability and reliability. The data were examined using the statistical analysis software of SPSS. The results of the analysis proved the validity of many hypotheses that were developed according to the hypothesis of the study. In general, the results of the tests demonstrated that the study model and hypotheses fulfilled statistically acceptable.